2015
DOI: 10.1021/acssynbio.5b00012
|View full text |Cite
|
Sign up to set email alerts
|

CRISPathBrick: Modular Combinatorial Assembly of Type II-A CRISPR Arrays for dCas9-Mediated Multiplex Transcriptional Repression in E. coli

Abstract: Programmable control over an addressable global regulator would enable simultaneous repression of multiple genes and would have tremendous impact on the field of synthetic biology. It has recently been established that CRISPR/Cas systems can be engineered to repress gene transcription at nearly any desired location in a sequence-specific manner, but there remain only a handful of applications described to date. In this work, we report development of a vector possessing a CRISPathBrick feature, enabling rapid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(150 citation statements)
references
References 61 publications
2
148
0
Order By: Relevance
“…One possible solution is the deletion or downregulation of the genes in competitive pathways. Previous work has indicated that the TCA cycle is likely to be a competitive pathway (35,38,39), and this work showed that deletion of the sucA gene in the TCA cycle does improve mevalonate yield. An alternative solution applied here is the enhancement of the downstream pathway for the desired product, and although it could not eliminate the production of by-products, it did increase the carbon flux to the desired product.…”
Section: Discussionmentioning
confidence: 75%
“…One possible solution is the deletion or downregulation of the genes in competitive pathways. Previous work has indicated that the TCA cycle is likely to be a competitive pathway (35,38,39), and this work showed that deletion of the sucA gene in the TCA cycle does improve mevalonate yield. An alternative solution applied here is the enhancement of the downstream pathway for the desired product, and although it could not eliminate the production of by-products, it did increase the carbon flux to the desired product.…”
Section: Discussionmentioning
confidence: 75%
“…Similar to lycopene, C3G in the colorimetric assay can be used as a screening molecule for desirable phenotypes in applications such as combinatorial engineering (37,38). The calibration curve generated could be utilized for rapid C3G concentration quantification without the need for complex and timeconsuming analytical tools.…”
Section: Resultsmentioning
confidence: 99%
“…1e). Several examples, such as the type III CRISPR-Csy4 [25,76] or natural CRISPR array [1,14] have been shown to efficiently generate multiple gRNAs from a single transcript (Fig. 1e).…”
Section: The Grna Characteristics and Extensionsmentioning
confidence: 99%
“…Method: CRISPR/Cas9-coupled recombineering mediated with the recombinase RecT Multiplexed repression with proof-ofconcept in naringenin production [14] CRISPRi Escherichia coli…”
Section: The Grna Characteristics and Extensionsmentioning
confidence: 99%
See 1 more Smart Citation